Response of Chickpea (Cicer Arietinum L.) To Boron and Molybdenum Fertilization - Hoque, A; Alam, MS; Khatun, S; Salahin, M (Journal of Bio-Science, 2021)
An experiment was conducted to study the effect of micronutrients on the growth and yield performance of chickpea. The experiment was consisted using two factors- variety and treatments. Two local cultivars viz. BARI Chola-5 and BARI Chola-9 and five treatments e.g. T0 = control, T1 = 2 kg B/ha, T2 = 2 kg Mo/ha, T3= seed priming with Mo (1g/l water), T4 = foliar spray of B (0.5 g/l water) + seed priming with Mo (1g/l water), and T5 = 2 kg B/ha + seed priming with Mo (1g/l water) were considered for this study. A randomized complete block design (RCBD) was adopted with three replications. Significant variation was observed between the varieties and here the BARI Chola-9 produced the higher seed yield (2.47 ton/ ha). Treatment showed significant effect on the yield attributes and yield of chickpea. The highest plant height, number of branches/ plant, number of pods/ plant, nodule/ plant, number of effective pod/ plant, length of the pod, 1000-grain weight, seed yield, straw yield, biological yield was obtained from T4. The highest seed yield (2.68 ton/ ha) was recorded from BARI Chola-9 with foliar spray of boron and seed priming with Mo. The results indicated that foliar spray of B and seed priming with molybdenum can be beneficial in improving growth and yield of chickpea variety BARI Chola-9. J. Bio-Sci. 29(2): 43-51, 2021 (December)